2014
DOI: 10.1038/ni.2925
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor IRF1 dictates the IL-21-dependent anticancer functions of TH9 cells

Abstract: The TH9 subset of helper T cells was initially shown to contribute to the induction of autoimmune and allergic diseases, but subsequent evidence has suggested that these cells also exert antitumor activities. However, the molecular events that account for their effector properties are elusive. Here we found that the transcription factor IRF1 enhanced the effector function of TH9 cells and dictated their anticancer properties. Under TH9-skewing conditions, interleukin 1β (IL-1β) induced phosphorylation of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
191
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 190 publications
(201 citation statements)
references
References 49 publications
6
191
2
2
Order By: Relevance
“…Moreover, Th9 cells release IL-21, which promotes the production of IFNg and tumor elimination by CD8 C T cells and NK cells. 113 The relevance of Th9 cells in thyroid oncogenesis remains to be elucidated. Fig.…”
Section: Natural Killer T Cells (Nkt) Gd T Cells and Innate Lymphoidmentioning
confidence: 99%
“…Moreover, Th9 cells release IL-21, which promotes the production of IFNg and tumor elimination by CD8 C T cells and NK cells. 113 The relevance of Th9 cells in thyroid oncogenesis remains to be elucidated. Fig.…”
Section: Natural Killer T Cells (Nkt) Gd T Cells and Innate Lymphoidmentioning
confidence: 99%
“…IRF1 is a Th1 transcription factor that is expressed in Th9 cells upon stimulation with IL1b. This factor binds directly on il9 and il21 promoters, and is essential to boost production of both cytokines (15). This factor is a powerful enhancer of the Th9 program.…”
Section: Transcriptional Program Of Th9 Cellsmentioning
confidence: 99%
“…Mouse and human Th9 cells secrete IL9 and IL21 and were initially proposed to contribute to the development of autoimmune and allergic diseases (11,12). We and others, however, recently found that Th9 cells also featured potent anticancer properties (13)(14)(15). In this review, we discuss the potential of using Th9 cells for anticancer immunotherapy.…”
mentioning
confidence: 97%
“…Ces cellules produisent également de l'IL-3 à des niveaux qui sont équivalents à ceux de l'IL-9 [15]. Jäger et al [16] Lorsque la polarisation par le TGF-b et l'IL-4 est associée à une exposition à une cytokine inflammatoire, l'IL-1b, une forte augmentation de la production d'IL-9 et d'IL-21 par les Th9 est observée [17]. Bien que produisant de l'IL-10, une cytokine anti-inflammatoire, les Th9 semblent dépourvus d'activité immunosuppressive [11], une absence de fonction suppressive qui n'est actuellement pas clairement expliquée.…”
Section: Les Cytokines Exprimées Par Les Lymphocytes Th9unclassified
“…La présence d'IL-1b lors de la polarisation, permet d'augmenter significativement l'activité antitumorale des Th9 ainsi différenciés par rapport à celle des Th9 conventionnels. Cette activité antitumorale est totalement neutralisée par l'adjonction d'anticorps bloquant l'IL-21 contrairement à celle des Th9 conventionnels qui dépend, elle, de la présence d'IL-9 [17]. L'IL-21 est une cytokine pléiotropique qui influence de nombreux types cellulaires : les lymphocytes T CD4 et CD8, les cellules Th17 et Treg, les cellules NK et NKT (T natural killer), les lymphocytes B, les cellules dendritiques et les macrophages [42].…”
Section: Maladies Auto-immunesunclassified